2012
DOI: 10.1063/1.4772060
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurements of the ionization profile in krypton helicon plasmas

Abstract: Single exposure three-dimensional imaging of dusty plasma clusters Rev. Sci. Instrum. 84, 023501 (2013) Hydrogen transport diagnostics by atomic and molecular emission line profiles simultaneously measured for large helical device Phys. Plasmas 20, 012514 (2013) Time-and-space resolved comparison of plasma expansion velocities in high-power diodes with velvet cathodes J. Appl. Phys. 113, 043307 (2013) Development of a diffuse air-argon plasma source using a dielectric-barrier discharge at atmospheric pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 17 publications
3
30
0
Order By: Relevance
“…This gives the physical appearance of a fuzzy broad core like structure even before the complete global transition. We believe that most helicon sources work in this mode of operation [10], [20], [22], [24]. If the maximum available magnetic field in this experiment was 130 mT, we would also have thought that we work in the helicon blue core mode.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This gives the physical appearance of a fuzzy broad core like structure even before the complete global transition. We believe that most helicon sources work in this mode of operation [10], [20], [22], [24]. If the maximum available magnetic field in this experiment was 130 mT, we would also have thought that we work in the helicon blue core mode.…”
Section: Discussionmentioning
confidence: 89%
“…The appearance of the core is typically used as an identification of the helicon mode [4], [13], [17], [20], [22]. The formation of a bright core is not restricted to argon helicon plasma, but has been observed for other working gases such as xenon [23] and krypton [24].…”
mentioning
confidence: 99%
“…Absolute densities have been measured in helicon plasmas in krypton in the CHEWIE device [84]. As expected, they show a linear increase in neutral density with fill pressure, and n n ≈ 10 20 m −3 at p = 3.6 mTorr.…”
Section: Neutral Depletion In the Plasma Coresupporting
confidence: 62%
“…Plasma density measurements indicate that the high-density core is approximately 1 cm in diameter. Two-photon absorption measurements of the absolute neutral density in another helicon source in our laboratory demonstrated that the core region is nearly 100% ionized in krypton helicon plasmas (Magee et al 2012a(Magee et al , 2012bGalante et al 2014). For the helium plasmas used in the Aflvén wave experiments, relative LIF measurements of the metastable neutral helium density also indicate a strong depletion of neutrals in the core.…”
Section: Experimental Regimes and Key Findingsmentioning
confidence: 96%